Harnessing the tumor microenvironment: targeted cancer therapies through modulation of epithelial-mesenchymal transition - Antonino Glaviano; Hannah Si-Hui Lau; Lukas M. Carter; E. Hui Clarissa Lee; Hiu Yan Lam; Elena Okina; Donavan Jia Jie Tan; Wency Tan; Hui Li Ang; Daniela Carbone; Michelle Yi-Hui Yee; Muthu K. Shanmugam; et al. (Journal of Hematology & Oncology)
Abstract The tumor microenvironment (TME) is integral to cancer progression, impacting metastasis and treatment response. It consists of diverse cell types, extracellular matrix components, and signaling molecules that interact to promote tumor growth and therapeutic resistance. Elucidating the intricate interactions between cancer cells and the TME is crucial in understanding cancer progression and therapeutic challenges. A critical process induced by TME signaling is the epithelial-mesenchymal transition (EMT), wherein epithelial cells acquire mesenchymal traits, which enhance their motility and invasiveness and promote metastasis and cancer progression. By targeting various components of the TME, novel investigational strategies aim to disrupt the TME’s contribution to the EMT, thereby improving treatment efficacy, addressing therapeutic resistance, and offering a nuanced approach to cancer therapy. This review scrutinizes the key players in the TME and the TME's contribution to the EMT, emphasizing avenues to therapeutically disrupt the interactions between the various TME components. Moreover, the article discusses the TME’s implications for resistance mechanisms and highlights the current therapeutic strategies toward TME modulation along with potential caveats.